PENGENDALIAN KUALITAS UNTUK MEMINIMALKAN CACAT PRODUK PIPA STAINLESS STEEL PADA PT. PPW - Dhoan Prasetyo Widanarko Cahyono; Siti Mundari (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Quality is an important key in a production process, especially in an increasingly developing era such as the current era of globalization. PT PPW is a company engaged in the stainless steel pipe industry. In the production process, there are three processes that use three production machines. Where the three machines still often experience defects in the second and third processes that exceed the tolerance standards set by the company. The problems that occur are the types of defects that arise in each process and what causes them, as well as how to minimize the number of defective products. Methods that can be used to identify defects and causes of defects can use the SPC method. Meanwhile, to minimize defective products, you can use FMEA analysis to implement the proposal according to the causes of the most critical defects. The results showed that the most critical types of defects were imperfect welds in the second process and imperfect polishing in the third work station. The cause of defects in the second work station was due to machine setting errors, while the causes of defects were due to the end of the polishing material and the physical condition of the product